Finite element analysis of long-span rail-cum-road cable-stayed bridge subjected to ship collision. Issue 11 (August 2019) - Pu, Qianhui; Liu, Jingwen; Gou, Hongye; Bao, Yi; Xie, Hongwei
Ship collision is rare, yet it leads to serious consequences once it occurs, in particular for long-span bridges. This study investigates dynamic responses of a long-span, rail-cum-road cable-stayed bridge under ship collision through finite element analysis. Three ship tonnages were investigated, which are 3000, 5000, and 8000 t, respectively. The displacement, velocity, and acceleration of the bridge under ship collision are analyzed. The collision process is simulated in two explicit steps to improve the computational efficiency. First, the collision force is determined through a collision simulation of the ship to a rigid body that simulates the massive bridge pier. The collision force is then applied to the bridge to analyze the dynamic responses of the bridge. The simulation results of the collision force are compared with four different design codes. Analysis results from different codes show significant discrepancies, demonstrating lack of reliability of the formula recommended by the codes. The results indicate that the maximum displacement and acceleration occur at the top of the bridge pylon. The bridge's responses under ship collision decrease as the collision angle increases from 0° to 20°.